Gabriele Stein. Better Words: Evaluating EFL Dictionaries. - Abecassis, Michaël (Lexikos, 2006)
Gabriele Stein, a Professor of English Linguistics at the University of Heidelberg, is one of the most authoritative academics in the study of English as a foreign language, and has published a wide range of research in the field of English lexicography. This book which is a collection of reprinted articles and previously unprinted papers, forms a cornerstone in EFL lexicography. It is a useful reference book for both EFL teachers and students alike, as well as for lexicographers.